An Review of World Lavender Oil Markets and Lessons for Turkey (International Journal of Innovative Research in Computer Science & Technology, 2021)
Lavender farms have lately grown in  popularity in Turkey. Lavender farming is becoming more  popular as a source of essential oils and rural tourism, which  raises a slew of concerns about production and marketing.  Turkey is known for its medicinal although it only  production increased oil, honeysuckle oil, and lemongrass oil  to the entire world, it is known for its fragrant plant and  fundamental gas production. The present interest in lavender  production in the nation has emphasized the need for a  deeper understanding and analysis of the worldwide lavender  oil markets. For worldwide lavender petroleum products and  commerce, however, numbers and a standardized  information are lacking. This study aims to bring aggregate  data, material, and expertise in terms of understanding and  evaluate the price and operators of lavender oil in worldwide  markets. Lavandula intermedia (lavandin) produces  practically all of Turkey's lavender, as well as the majority  of the world's lavender. Although lavandin essential oil is  five times more expensive than L. angustifolia (genuine  lavender) oil, L. angustifolia oil has been the most respected  and wanted after almond oil. Bulgaria, France, and China are  the world's biggest lavender oil exporters, although several  other nations have lately boosted their output. The global  supply of lavender oil has tended to rise as plantations in  Bulgaria have grown, although quantity and quality are  dependent on climatic conditions. The primary driver of  price determination is lavender oil demand, which does not  change much from year to year. Increased consumer  awareness of healthier goods made with natural and organic  components, on the other hand, is anticipated to drive up  demand. The issue is whether Turkey has the potential to  become a global participant in the lavender oil industry.  Lavender production is appealing because of its Despite its  cheap operating costs, better profit rate, and significance in  rural development, lavender petroleum is economically  unviable for people going separately due to small farm sizes  and a convoluted value chain, requiring them to stay at the  outset of the production process. However, since good  lavender oil would still have an industry, Hungary should  depend on the effectiveness and structure of the entire value chain to be competitive in the marketplace.
Keywords: Angustifolia; Lavandula Lavender Oil; Lavender Oil Markets; Value Chain